Anti- Phospholipid Antibodies in Multiple Blood Transfusion Dependent β-Thalassemia Major Patients at Hyderabad (Medical Forum Monthly, 2024)
Objective: The study aimed to observe the anti-phospholipid antibodies in multiple blood transfusion dependent β-thalassemia patients at the Hyderabad.Study Design: Observational / cross sectional study.Place and Duration of Study: This study was conducted at pathology and pediatric department, Liaquat University of Medical & Health Sciences, Jamshoro, from June 2013 to May 2015.Material and Method: A total of 121 patients were enrolled. Blood samples were collected in citrated tube. APTT was performed on Sysmex (CA 500) while Lupus anticoagulant and Anticardiolipin antibodies were performed on commercial kits.Results: Of 121 patients 81(66.9%) patients were positive for anti-phospholipid antibody while 40(33.1%) were negative. Lupus anticoagulant were present in 69 (57%) and were not detected in 52 (43%). Cardiolipin antibodies were found positive in 45 (37.2%) while negative in 76 (62.8%) cases.Conclusion: Anti-phospholipid is common in patients with beta thalassemia major. APLs are considered as a common acquired autoimmune hyper coagulation state for thrombotic risk factor.